Effect of Thermal Activation on the Mineralogical Structure of Magnesium Slag - Korkmaz, Abdul Vahap (International Journal of Computational and Experimental Science and Engineering, 2024)
Magnesium slag’s production process is similar to the Portland cement production process. The raw material used is carbonate-containing dolomite, and is calcined in a rotary kiln at 850-900 oC. Afterwards, ferrosilicon and fluorite raw materials are added to the calcined material, they are ground together and turned into pellets, and then they are reduced at a temperature close to the firing temperature of Portland cement clinker (1250-1350 oC) to obtain crown magnesium and magnesium slag. The reduction time of pellet material in reduction furnaces is 12 hours. During this period, almost all of the magnesium minerals in the mixture material are reduced and taken as crown magnesium metal. The remaining material, described as magnesium production slag (reduction furnace waste), consists of Alite (C3S), Belite (C2S), Celite (C3A) and C4AF minerals contained in Portland cement clinker. Some of the minerals contained in Portland cement clinker in the rotary kiln are formed at temperatures below 1400 °C, which is the clinker firing temperature. The only difference other than the firing temperature is that after the Portland cement clinker is fired in the rotary kiln, the clinker is cooled rapidly, increasing the alite (C3S) crystals formed in its structure and preventing the alite minerals from turning back into belite (C2S) minerals. This study produced magnesium slags at different temperatures (1200-1350 oC) by thermal activation method in an industrial environment. The Bogue and XRD methods calculated the mineral phase amounts of the products produced.